Payout policy, taxes, and the relation between returns and the bid–ask spread - Gottesman, Aron A.; Jacoby, Gady (Journal of Banking & Finance, 2006)
Recent evidence demonstrates that corporate payout policy has shifted from the nearly exclusive use of dividend payout to the inclusion of stock repurchase, primarily through open markets. This trend has been attributed to the tax advantages associated with repurchase relative to dividends. In this paper, we introduce personal taxation and stock repurchase to reexamine the relation between returns and the bid–ask spread. Our model provides insight into the nature of this relation. Tests performed using NYSE, AMEX, and NASDAQ data provide empirical support of our theoretical conclusions. We conclude that the firm’s choice of payout policy influences the relation between returns and spreads.